The Effect of Safety Training and Supervision on The Use of Personal Protective Equipment Which Has Implications on Work Safety in Loading and Unloading at Maccini Baji Port, Maros, South Sulawesi - Muhammad Al Imadudin; Yovananda Bayudewa Kusumawardhana; Hasbi Aziz Ashshidddiqi; Bambang Sumali (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
This study aims to analyze the influence of training and safety supervision on the use of personal protective equipment (PPE) and its implications for loading and unloading safety at Maccini Baji Port, Maros, South Sulawesi. The issues addressed include the low awareness and compliance of workers in using PPE and the lack of adequate safety supervision. The research population consists of 155 employees and dockworkers at the port, with a saturated sampling technique used. The research method employed is quantitative, with data collected through questionnaires and observations. Data analysis was conducted using the SMART PLS method. The results show that training and safety supervision have a positive and significant effect on the use of PPE, which also has a positive implication for loading and unloading safety. Training proved to be effective through the instructor dimension, while safety supervision was greatly influenced by the accuracy of measurement. In conclusion, improving the quality of training and supervision can enhance compliance with PPE usage and work safety at the port. Managerial recommendations include increasing the frequency of training, maintaining equipment, and regularly supervising PPE usage by introducing more accurate and modern monitoring technologies.